Pemanfaatan Google Form Untuk Ujian Akhir Semester D III Farmasi Sebagai Persiapan Menghadapi Ujian Kompetensi - Mhd. Riza Marjoni; Indrie Ramadhani; ‘Ainun Naim; Zulfisa Zulfisa (Abdimas Mandalika, 2022)
Abstract:  Cheating in the final semester examination process by Paper base test (PBT) is unavoidable and the slow correction process which results in late input of final grades into student Study Results Cards. To overcome various kinds of cheating in the final exam, this community service activity was carried out. The purpose of this activity is to design an online final semester exam application by utilizing the google form to overcome delays in the conventional exam system. This activity is also an introduction to D III Pharmacy students about the competency exam system based on the Computer Base Test (CBT) system which is carried out online. The system in this exam is designed to be similar to the actual competency exam, starting from writing questions with a vignette, multiple choice with 5 answer choices, time discipline for 1 question 1 minute to evaluating the final results obtained by students shortly after the exam is over. The method used in this community service consists of several stages: survey, activity preparation, socialization, implementation and evaluation. The result of this service activity which is centered at the Dwi Farma Bukittinggi Pharmacy Academy is an increase in the understanding and skills of lecturers in designing online exams by utilizing the google form. This community service activity is also able to improve the understanding and skills of D III Pharmacy students about the online-based Competency Exam system.Abstrak: Kecurangan yang terjadi pada proses ujian akhir semester secara Paper base test (PBT) tidak dapat dihindari serta lambatnya proses koreksi yang mengakibatkan terlambatnya input nilai akhir kedalam Kartu hasil Studi mahasiswa. Untuk mengatasi berbagai kecurangan dalam ujian akhir tersebut, maka dilakukan kegiatan pengabdian ini. Tujuan dari kegiatan ini adalah merancang aplikasi ujian akhir semester berbasis online dengan memanfaatkan google form dalam rangka mengatasi kelambanan yang terjadi pada system ujian konvensional dan Kegiatan ini juga sekaligus pengenalan kepada mahasiswa D III Farmasi tentang system ujian kompetensi yang berbasis Computer base Test (CBT) yang dilaksanakan secara online. Sistem pada ujian ini dirancang menyerupai ujian kompetensi yang sebenarnya mulau dari penulisan soal dengan vignette, pilihan ganda dengan 5 pilihan jawaban, pendisiplinan waktu 1 soal 1 menit  sampai pada evaluasi hasil akhir yang diperoleh oleh mahasiswa sesaat setelah ujian berlangsung. Metoda kegiatan yang digunakan pada pengabdian ini terdiri dari beberapa tahapan yaitu survey kebutuhan, persiapan, sosialisasi, pelaksanaan dan evaluasi. Hasil kegiatan pengabdian yang dipusatkan di Akademi farmasi Dwi Farma Bukittinggi ini adalah peningkatan pemahaman dan keterampilan dosen dalam merancang ujian online dengan memanfaatkan google form serta meningkatnya pemahaman dan keterampilan mahasiswa D III Farmasi tentang system Ujian Kompetensi berbasis online..